Assessment of permanent magnets and electropositive metals to reduce the line-based capture of Galapagos sharks, Carcharhinus galapagensis - Robbins, William; Peddemors, V.; Kennelly, S. (Elsevier BV, 2011)
Sharks possess anterior electrosensory pores (ampullae of Lorenzini), which allow them to detect very weak electromagnetic fields. Powerful magnetic fields may overwhelm this sense, and repel sharks, even in the presence of an attractant. Using underwater video, we tested seven rare earth magnet configurations, two ferrite magnet configurations and two rare earth electropositive metals as means to reduce the rate at which Galapagos sharks (Carcharhinus galapagensis) depredated baited lines. Configurations of three 50. mm diameter rare earth magnet discs showed the most potential, with a vertical configuration of magnets alongside the bait reducing depredation by 50%, and a stacked configuration of the same magnets above the bait also producing significantly more aborted investigations of the bait prior to depredation. No other magnetic or electropositive metal configuration produced significant reductions in depredation rates, time taken to strike, or number of prior investigations. Our study showed that the overriding factor determining Galapagos shark behaviours towards baits was conspecific density. The number of sharks present increased as trials progressed, with a corresponding decrease in their time to depredate baits. This effect was particularly apparent when three or more animals were present. These higher shark densities diminished the effectiveness of our experiments as individuals engaged in non-selective " mob" rushes towards the closest bait. Although our results showed that social interactions between sharks outweighed individual responses to depredation-mitigation devices, magnetic deterrents have high potential for reducing shark bycatch for species that occur in lower densities, or which interact less vigorously with conspecifics than Galapagos sharks. © 2011.